2017
DOI: 10.3390/e19120679
|View full text |Cite
|
Sign up to set email alerts
|

Second-Law Analysis: A Powerful Tool for Analyzing Computational Fluid Dynamics (CFD) Results

Abstract: Second-law analysis (SLA) is an important concept in thermodynamics, which basically assesses energy by its value in terms of its convertibility from one form to another. Highly-valued forms of energy in this context are called exergy, defined as those energies from which the maximum theoretical work is obtainable when the energy is interacting with the environment to equilibrium (see Moran et al. [1], for example).The counterpart of exergy, also called available work, is anergy, so that with this concept ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Plotted in Figure 12 , it can be seen that the high values of remain almost the same with with time evolution, which indicates that the thermal entropy generation rate plays a dominated role in the heat transfer irreversibility—the viscous entropy generation can be neglected time evolution. The above phenomenon is well consistent with the importance of heat transfer irreversibility in the previous studies [ 23 , 24 , 25 ]. Wei et al [ 24 ] studied the effect of changing the Prandtl number on the entropy generation rate in two-dimensional RB convection, and argued that the thermal entropy generation rate has a dominant role in the heat transfer irreversibility—the viscous entropy generation can be neglected with the increasing Prandtl number.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Plotted in Figure 12 , it can be seen that the high values of remain almost the same with with time evolution, which indicates that the thermal entropy generation rate plays a dominated role in the heat transfer irreversibility—the viscous entropy generation can be neglected time evolution. The above phenomenon is well consistent with the importance of heat transfer irreversibility in the previous studies [ 23 , 24 , 25 ]. Wei et al [ 24 ] studied the effect of changing the Prandtl number on the entropy generation rate in two-dimensional RB convection, and argued that the thermal entropy generation rate has a dominant role in the heat transfer irreversibility—the viscous entropy generation can be neglected with the increasing Prandtl number.…”
Section: Resultssupporting
confidence: 92%
“…In order to understand the global flow and heat transport loss mechanisms in detail, we will present the detailed statistical characteristic mechanisms of the velocity and temperature gradient fields, in particular the related viscous and thermal local entropy generation rates. The viscous and thermal local entropy generation rates as a criterion are used to provide insight into the local viscous and thermal flow loss in the flow field [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The viscous and thermal components of the local entropy generation rate are derived in the two-dimensional Cartesian space [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…reported the influence of different Prandtl numbers on the entropy generation in thermal convection. Jin [ 25 ] demonstrated that entropy is a powerful approach to analyze the computed results by second-law analysis. The local entropy generation rate that contains a large amount of phenomenological information are studied by many researchers, e.g., [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], Pizzolato et al [ 26 ], Rejane et al [ 27 ], Mahian et al [ 28 ], Sheremet et al [ 29 ], Bhatt et al [ 30 , 31 ], Abbas et al [ 32 ] and Qing et al [ 33 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 20 ] discovered that discrete heat boundary conditions can affect entropy generation in natural convection. Jin [ 21 ] reported that entropy is a powerful method by the tool of Computational Fluid Dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [20] discovered that discrete heat boundary conditions can affect entropy generation in natural convection. Jin [21] reported that entropy is a powerful method by the tool of Computational Fluid Dynamics. Based on the above discussions, the statistics of the viscosity and thermal entropy generation rates in two-dimensional RT turbulence by means of data obtained from the lattice Boltzmann method are investigated in this paper.…”
Section: Introductionmentioning
confidence: 99%